Pengaruh Pendidikan Kesehatan terhadap Tingkat Pengetahuan Remaja tentang Dismenore dan Penanganan Non Farmakologi di SMAN 3 Kupang - Karunia Natalia Manafe; Apris A. Adu; Helga J. N. Ndun (Media Kesehatan Masyarakat, 2021)
Menstruation is the periodic production of blood, mucus and epithelial cells from uterus. Some women feel pain in the abdomen that comes from the uterine cramps that can spread to the lower back and limbs. This condition is known as dismenorrhea and occurs before and during menstruation. Dismenorrhea is thought to be derived from uterine contractions stimulated by prostaglandin. The purpose of the study was to analyze the influence of health education on the level of knowledge of the teenagers in SMAN 3 Kupang. This kind of research is quasi-experimental with one group pra post test design. The subjects for this experimental study will be 521 girls at Grade X and XI in SMAN 3 Kupang. The sampling techniques are using proposional stratified random sampling with the number of samples of 84 girls. The variables studied are using wilcoxon test. The result showed that there was an increase in girls' knowledge after being given a health knowledge, with the avarage score for 69,26 at pretest increased to 88,9 in the post test, with significant value of ρ = 0,000 or smaller value is α = 0,05, so health education affects to the improvement of adolescent knowledge about dismenorrhea and non-pharmacological treatment.